Pelatihan Penyusunan Perangkat Perencanaan Pembelajaran Kepada Para Guru - Sulastri, Sulastri (Jurnal Loyalitas Sosial, 2019)
In order to implement the learning process that has been established in the syllabus, the teacher must develop a Learning Implementation Plan (RPP). RPP is a handle for teachers in carrying out learning both in class, laboratory, and / or field to achieve every basic competency. Therefore, what is contained in the RPP contains matters that are directly related to learning activities in an effort to achieve mastery of each of the Basic Competencies. But in reality there are difficulties in arranging learning planning tools namely RPP, Prota, and Prosem. The method of activity used is by survey. After being given training in the preparation of learning device planning, the teacher councils are more understanding and able to develop learning devices well again. Increased teacher understanding in developing learning devices increased from 50% to 91.6%. Therefore, the community service activities provided in the form of training provide a useful learning experience according to the needs of the board of teachers and dedicated lecturers. Dedication activities especially in providing this training must continue to be carried out to help improve the skills of the teachers in developing learning devices.